Cerebellar Hypoplasia and Autism - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The size of the cerebellar hemisphere and vermal lobules was measured in ten autistic and eight normal control subjects at the Neuropsychology Research Laboratory, Children's Hospital Research Center, and the Departments of Neurosciences and Radiology, School of Medicine, University of California at San Diego, LaJolla.